Transcriptomics studies under water-deficit stress: towards genetic improvement of Bambara groundnut (Vigna subterranea (L.) Verdc.) - Khan, Faraz (2017)
With the world population estimated to be nine billion by 2050, the need to exploit plant genetic diversity in order to increase and diversify global food supply, and minimise the over-reliance for food on a few staple crops is of the utmost importance to address food security challenges. Bambara groundnut (Vigna subterranea (L) Verdc.), is an underutilised legume indigenous to Africa, rich in carbohydrates, with reasonable amounts of protein. It is known to be drought tolerant, able to grow on marginal lands where other major crops cannot with minimal rainfall (<700 mm) and no chemical inputs. The present study aimed to investigate and evaluate transcriptomic changes in two bambara groundnut genotypes; DipC and TN (Tiga Nicuru), derived from landraces, in response to drought stress using microarray XSpecies and next generation RNA sequencing approaches by utilising data, resources and approaches derived from major crops and model plants. Crop improvement for abiotic stress tolerance and increasing/stabilising yield have been difficult to achieve due to the complex nature of these stresses, and the genotype x environment interaction (GxE). Using bambara groundnut as an exemplar species this study also highlights how a number of recent technologies and approaches used for major crop research, can be translated for use in the research of minor crops for a better understanding of the genetics governing drought traits. To investigate the drought tolerance of bambara groundnut, microarray XSpecies and next generation RNA sequencing (RNA-seq) analysis was completed on leaf tissue from DipC and TN under drought and control (irrigation) conditions at different developmental stages (vegetative, reproductive and pod development). This is the first drought experiment reported in bambara groundnut employing the RNA-seq approach. Both investigation of mild (microarray XSpecies) and relatively severe (RNA-seq) drought stress for the DipC and TN genotypes, adapted to similar environmental conditions, provided initial evidence that the two genotypes used different sets of genes to achieve drought response traits (including; ABA synthesis, hormone signaling, osmotic adjustment, accumulation of antioxidants, lignin synthesis, down-regulation of photosynthesis related genes, carbohydrate metabolism, cell-wall modification and transporters). Hence, both genotypes may have adapted in different ways to enable them to grow in the semi-arid conditions, suggesting that there may be more than a single way to achieve resilience in the face of drought stress. The key enzymes involved in metabolic pathways, such as carbohydrate metabolism, redox homeostasis, lipid metabolism, photosynthesis, generation of precursor metabolites/energy, and cell wall component biogenesis were affected by drought stress in both genotypes. XSpecies microarray experiment identified several differentially expressed genes (DEG) in each genotype and the four potential drought candidate genes (PAL1, Beta-fructofuranosidase, COMT, UBC-2) identified were validated utilising quantitative reverse transcriptase PCR (qRT-PCR). In addition, both drought experiments (mild and severe) also showed that the two genotypes expressed a number of genes of what are classically considered to be ‘drought-response’ genes even under the control condition. These results suggest that high expression of drought-response genes even under control conditions in both genotypes may lead to greater root growth and other avoidance traits which prime the plant for future dry periods, hence preparing for drought conditions. Morphological differences and the rapid reduction in photosynthesis, stomatal conductance and transpiration observed in both genotypes under drought stress provides a platform to link these physiological data with gene expression data. The observed physiological responses (i.e reduction in stomatal conductance and photosynthesis) under drought stress were backed up by high expression of genes related to stomatal closure via ABA signaling and down-regulation of photosynthesis-associated genes. A selection of genes chosen from microarray XSpecies and RNA-seq experiments were further used to identify their approximate chromosomal location in bambara groundnut using a cross-species approach. A total of 4 genes (HOX, AUX_IAA, acid phosphatase and dehydrin) were found to be near or within the confidence intervals of the QTLs underlying two drought traits (stomatal density/leaf area and CID). The initial results suggest that some of the locations of genes identified in XSpecies microarray and RNA-seq experiments could underlie QTL involved in controlling drought traits in bambara groundnut. These data provide the basis for drought trait improvement in bambara groundnut, which will facilitate functional genomics studies. Analysis of this dataset have suggested that both genotypes are primed to respond to drought stress and have adapted in different ways to achieve drought tolerance. This will help in understanding the mechanisms underlying the ability of crops to produce viable yields under drought conditions. Future work should verify whether the identified genes are associated with the trait of interest.